O15.1 'A PrEP user is someone who has a lot of bareback': a qualitative study of acceptability of PrEP in MSM in lebanon. (14th July 2019) - Maatouk, Ismael; Jaspal, Rusi
Abstract : Background: Pre-exposure prophylaxis (PrEP) is a significant development in the global efforts to prevent HIV transmission and acquisition. In order to realize the potential of this antiretroviral medication for preventing acquisition of the virus by HIV-negative people, it is crucial to understand how it is perceived by most-at-risk populations and to assess their willingness to use it. PrEP have been shown to be effective in preventing HIV in MSM. The aim of this qualitative research was to understand the willingness of MSM in Lebanon to use PrEP, including their perception of it, its effectiveness, as well as potential motivators for and barriers to its uptake. Methods: Interviews were conducted with 18 Lebanese MSM using an STI clinic and checkpoint in Lebanon. Data were analyzed using Qualitative Thematic Analysis. Results: All participants recognized that PrEP reduces the risk of HIV acquisition and frequently positioned it as an alternative to condoms. Perceived barriers to PrEP included one's lack of discipline to adhere to PrEP adequately, the risk of potential side effects, the stigma surrounding PrEP and its users, and the potential cost of acquiring PrEP. Conclusion: Findings from this qualitative study suggest that in principle PrEP may be acceptable to MSM in Lebanon but that there are significant barriers to its uptake that need to be addressed before its implementation. Greater awareness and understanding of PrEP are critical to its successful implementation in Lebanon. Furthermore, its implementation needs to be matched by an adequate stigma reduction campaign. Disclosure: No significant relationships.